Using the Posttraumatic Growth Inventory–Short Form With Palestinian Helpers Living in Conflict Areas. (3rd July 2019) - Veronese, Guido; Pepe, Alessandro
Abstract: This study was designed to evaluate the dimensionality, internal consistency, and validity of scores on the Arabic Post-Traumatic Growth Inventory–Short Form (PTGI–SF). This brief 10-item form of the PTGI self-report measure was administered to a sample of Arabic-speaking professional helpers ( N = 338) working in Israel, Gaza, and the West Bank. Scores were assessed using confirmatory factor analysis. The findings suggest that the psychometric properties of the Arabic version of the PTGI–SF make it appropriate for assessing posttraumatic growth in the broader Arabic-speaking population.